2020
DOI: 10.1371/journal.pone.0234241
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to measuring knowledge among frontline health workers in India: Are phone surveys a reliable option?

Abstract: Background In 2017, India was home to nearly 20% of maternal and child deaths occurring globally. Accredited social health activists (ASHAs) act as the frontline for health services delivery in India, providing a range of reproductive, maternal, newborn, child health, and nutrition (RMNCH&N) services. Empirical evidence on ASHAs' knowledge is limited, yet is a critical determinant of the quality of health services provided. We assessed the determinants of RMNCH&N knowledge among ASHAs and examined the reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“… 25 26 This points to insufficient counselling by FLHWs on infant nutrition and gaps in frontline worker knowledge and capacity. 27 While most qualitative respondents were similarly satisfied with their traditional approaches to family planning, several did acknowledge the fallibility of these methods and almost all wanted to space pregnancies and have just two or three children provided they had at least one son. A single digital direct-to-beneficiary behaviour change communication intervention is very unlikely to change deeply entrenched social and behavioural norms, such as son preference and child feeding behaviours.…”
Section: Discussionmentioning
confidence: 98%
“… 25 26 This points to insufficient counselling by FLHWs on infant nutrition and gaps in frontline worker knowledge and capacity. 27 While most qualitative respondents were similarly satisfied with their traditional approaches to family planning, several did acknowledge the fallibility of these methods and almost all wanted to space pregnancies and have just two or three children provided they had at least one son. A single digital direct-to-beneficiary behaviour change communication intervention is very unlikely to change deeply entrenched social and behavioural norms, such as son preference and child feeding behaviours.…”
Section: Discussionmentioning
confidence: 98%
“…First, a conceptual framework was developed comprised of factors believed to influence pregnant women's knowledge from previous literature (figure 2). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] At the individual level, characteristics such as phone ownership, healthcare characteristics, socioeconomic and sociodemographic factors were considered. A wealth index was created by dividing the women into five quintiles using principal component analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This cadre of FLHW is the largest of its kind globally, and once deployed ASHAs tend to remain in service for extended periods of time (Findings: cross-sectional surveys among ASHAs in Madhya Pradesh found that 60% of ASHAs had been in service for 4–10 years, 27% for 10+ years and 13% for <4 years. 25 ). Given the volume of providers, and the length of time they remain in-service, low-cost alternatives to in-person training strategies are needed.…”
Section: Summary Learnings and Implications For Future Programmingmentioning
confidence: 99%